2010
DOI: 10.3171/2009.9.spine09272
|View full text |Cite
|
Sign up to set email alerts
|

Which lumbar interbody fusion technique is better in terms of level for the treatment of unstable isthmic spondylolisthesis?

Abstract: Object The purpose of this study was to investigate and compare clinical and radiographic outcomes of 2 kinds of lumbar interbody fusion (LIF) for the treatment of adult low-grade isthmic spondylolisthesis at L4–5 and L5–S1 levels. Methods The medical records and radiographs of 86 patients who underwent anterior LIF (ALIF) (L4–5, 42 patients; L5–S1, 44 patients) and 42 patients who underwent transforamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 36 publications
2
46
0
6
Order By: Relevance
“…22,23 As with previous studies, our results also show that disc height restoration, both anterior and posterior, is better achieved with interbody cage placement, as LLIF, ALIF and TLIF all yielded significant improvements post-operatively, whereas PSF did not. [24][25][26] In fact the post-operative posterior disc height in PSF decreased significantly compared to baseline. Bilateral pedicle screws were used to augment all the PSF procedures.…”
Section: Discussionmentioning
confidence: 95%
“…22,23 As with previous studies, our results also show that disc height restoration, both anterior and posterior, is better achieved with interbody cage placement, as LLIF, ALIF and TLIF all yielded significant improvements post-operatively, whereas PSF did not. [24][25][26] In fact the post-operative posterior disc height in PSF decreased significantly compared to baseline. Bilateral pedicle screws were used to augment all the PSF procedures.…”
Section: Discussionmentioning
confidence: 95%
“…Guerin et al [3] performed an anatomical study on the safe working zones inside the psoas muscle and found that at L3-4 and L4-5 levels, the ''safest'' zone is always posterior to genitofemoral nerve. Anterior lumbar interbody fusion is another alternative to XLIF [8][9][10][11][12][13][14][15][16][17][18][19]. However, there are several limitations associated with this ALIF.…”
Section: Discussionmentioning
confidence: 99%
“…interbody fusion can support the anterior column, reduce slippage, minimize posterior injury, and restore disc height to achieve indirect neural decompression [4,5,15,16,22].…”
mentioning
confidence: 99%